Case Report: Acute myocarditis in a patient with Duchenne muscular dystrophy - Zhang, Xinyuan; Guo, Yingkun; Xu, Huayan (Frontiers in Cardiovascular Medicine, 2024)
Background Cardiovascular complications are the leading cause of death among individuals with Duchenne muscular dystrophy (DMD). However, due to the difficulty in evaluating individuals with inactive DMD, acute myocardial injury may be overlooked. Case presentation An 11-year-old boy with DMD presented to the emergency department with a 5-day history of persistent nasal congestion, runny nose, and cough. He was regularly taking prednisolone acetate, angiotensin-converting enzyme (ACE) inhibitors, and β-blockers for suspected DMD-associated cardiomyopathy. Upon presentation, a substantially elevated cardiac troponin I (cTnI) level of 19.8 μg/L and abnormal electrocardiogram (ECG) results were detected. Further cardiac magnetic resonance imaging (CMR) showed myocardial inflammation with localized T2 hyperintensity from the basal to middle lateral and inferior walls, as well as late gadolinium enhancement (LGE) from the basal to apical inferior lateral walls, supporting a diagnosis of acute myocarditis. Subsequently, the patient showed clinical improvement in response to combination treatment with intravenous immunoglobulin, oral prednisolone acetate, potassium chloride sustained-release tablets, anti-heart failure medication, and broad-spectrum antibiotics. Conclusions We report a rare case of acute myocarditis in a patient with DMD, potentially due to upper respiratory tract infection. This case highlights the importance of early myocarditis recognition and treatment in patients with DMD.